Elevated glutathione synthesis in leaves contributes to zinc transport from roots to shoots in Arabidopsis. (June 2019) - Wongkaew, Arunee; Nakamura, Shin-ichi; Suzui, Nobuo; Yin, Yong-Gen; Ishii, Satomi; Kawachi, Naoki; Kojima, Katsuhiro; Sekimoto, Hitoshi; Yokoyama, Tadashi; Ohkama-Ohtsu, Naoko
Highlights: GSH participates in Zn transport from root to shoot when Zn levels are adequate. Transgenic Arabidopsis with enhanced foliar GSH synthesis were generated. Elevated foliar GSH concentration increased phloem loading of GSH. Enhancement of foliar GSH synthesis increased Zn concentrations in the shoots. Abstract: Glutathione (GSH) is a vital compound involved in several plant metabolic pathways. Our previous study indicated that foliar GSH application can increase zinc (Zn) levels in leafy vegetables. The objective of this study was to determine the mode of action of GSH as it relates to Zn transport from roots to shoots. Two types of transgenic Arabidopsis plants with genes for GSH synthesis, including StGCS-GS or AtGSH1 driven by the leaf-specific promoter of chlorophyll a /b-binding protein ( pCab3 ) gene were generated. Both types of transgenic Arabidopsis plants showed significant increases in shoot GSH concentrations compared to the wild type (WT). Monitoring 65 Zn movement by positron-emitting tracer imaging system (PETIS) analysis indicated that the 65 Zn amount in the shoots of both types of transgenic Arabidopsis plants were higher than that in the WT. GSH concentration in phloem sap was increased significantly in WT with foliar applications of 10 mM GSH (WT-GSH), but not in transgenic Arabidopsis with elevated foliar GSH synthesis. Both types of transgenic Arabidopsis with elevated foliar GSH synthesis and WT-GSH exhibited increased shoot Zn concentrations and Zn translocation ratios. These results suggest that enhancement of endogenous foliar GSH synthesis and exogenous foliar GSH application affect root-to-shoot transport of Zn.